Behind the curtain: unveiling the challenges faced by daily wage teachers in Khyber Pakhtunkhwa universities, Pakistan - Daraz, Umar; Khan, Younas; Alsawalqa, Rula Odeh; Alrawashdeh, Maissa N.; Alnajdawi, Ann Mousa; Aziz, Tariq (Frontiers in Sociology, 2025)
This study examines the multifaceted challenges faced by daily wage teachers in Khyber Pakhtunkhwa, Pakistan, encompassing social, economic, academic, administrative, and psychological dimensions. The primary objective is to analyze how systemic barriers perpetuate precarious employment conditions and to propose actionable solutions for improving their wellbeing and professional experiences. Social exclusion and inadequate support within academic settings foster feelings of isolation, while the economic instability of per-class payment models exacerbates financial insecurity, leading to diminished morale. Academically, career stagnation persists as these teachers' qualifications and contributions are often undervalued. Additionally, administrative inefficiencies and exploitative practices erode trust and exacerbate their precarious status. Psychological challenges, including heightened anxiety and depression, are prevalent among this population. Using a phenomenological approach, the study employs purposive sampling, semi-structured interviews, and focus group discussions to explore these issues. Thematic analysis reveals the systemic barriers reinforcing the marginalization, financial instability, and administrative hurdles experienced by daily wage teachers. Key findings emphasize the need for targeted reforms, such as mentorship programs to enhance social integration, stable salary structures to ensure financial security, clear pathways for career progression, streamlined administrative processes, and accessible mental health support. The study highlights the urgency of addressing these challenges through inclusive and evidence-based policy measures, advocating for structural changes to improve working conditions and foster equity within the academic landscape.